Arctic Hysteria in Salem? - Zeller, Anne C. (Anthropologica, 2022)
The outbreak of "witchcraft" in Salem was the most widespread of several similar occurrences in late 17th-century New England. Although many people later became involved in accusations and counter-accusations, the original 8 to 10 afflicted girls were affected by a behaviour-altering phenomenon which their contemporaries did not recognize as having natural causes. It was more than a month later that witchcraft was diagnosed. In this paper I am suggesting that the original cause of the behavioural abnormalities may have been the condition now called pibloktoq or Arctic hysteria. The cause of this behavioural anomaly is not completely understood but there is a substantial argument that it is influenced by low or fluctuating levels of calcium cations (hypo-calcemia) which also reciprocally affect the phosphate balance. The running, yelling, convulsive behaviours manifested are very similar in the two conditions although they may easily have been regarded as unnatural in 1692, since the phenomenon of pibloktoq was not diagnosed until the late 19th century. Data concerning diet, light levels and activity patterns of 17th century lifestyles are drawn from recorded information and indicate that calcium levels may indeed have been low in young women of that time period. If skeletal material were available for examination it is possible that metabolic deficiencies could be ascertained, but at present such material cannot be located.